Benefits of Nigerian Migrant Associations: The Role of Nigerian Migrants in Nigerian Migrants integration and Adjustment Prospects in Accra, Ghana - Adzah, Y.W. (My University, 2018)
Migrant associations in different part of the world have been acknowledged by scholars due to the current expansion of such associations and their roles in the integration and adjustment processes for their members in host communities within destination countries. Though these associations have become globalized, existing literatures mostly focus on those in the developed countries like the USA especially migrants from Central and Latin America. Generally, in Ghana and Africa, literature on migrants associations are scanty as a result of absence of proper structures to monitor the affairs of these associations as well as the bureaucratic challenges when registering a group or an association. The study sought to tease out the benefits derived from migrants associations namely Nigerian Committee of Brothers, Nigerian Women and Edo State associations in Accra, Ghana and how members of these associations rely on them to ensure adjustment, integration and development. The study relied on secondary data retrieved from different sources as well in-depth interviews from five (5) key informants selected purposively from the associations. The study revealed that social network binds Nigerian migrants in complex social and interpersonal relationship away from their usual kinship-oriented networks (eg family system) using the associations as a substitute. The inability of Ghanaian state institutions to handle migrant needs effectively, the associations play expert roles to ensure their adjustment and integration into Ghana. Although the associations don’t serve as a direct mode of economic development, their social activism makes them useful social development agents in Ghana.
Thesis (MA)
Keywords: Migrant Associations; Nigerian Migrants; integration and Adjustment; Accra; Ghana